THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION (PMR) ON SLEEP QUALITY IN ELDERLY - Suhendra Agung Wibowo; Ifa Nofalia (Journal of Health, Sport, and Nursing, 2025)
Introduction: Sleep disturbances are a common and pressing health issue among the elderly, significantly impacting their overall well-being and quality of life. Purpose: To examine the effect of Progressive Muscle Relaxation (PMR) on sleep quality in elderly individuals. A quantitative pre-test and post-test design was employed with 20 elderly participants aged 60 to 90 years. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after the PMR intervention. Method: Results showed that prior to the intervention, 90% of participants experienced mild sleep disturbances and 10% had moderate disturbances. Following the intervention, 20% of participants reported good sleep quality, and none remained in the moderate disturbance category. The Wilcoxon signed-rank test revealed a significant difference between pre- and post-intervention PSQI scores (Z = -3.920, p = 0.000), indicating a significant reduction in sleep disturbances after PMR. Conclusion: These findings suggest that PMR is effective in improving sleep quality among the elderly. The study recommends further development of PMR programs as a non-pharmacological intervention to enhance sleep health in older populations across various settings.